2017
DOI: 10.1161/jaha.117.006458
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Is Associated With Autophagy and Cardiomyocyte Remodeling in Experimental and Human Atrial Fibrillation

Abstract: BackgroundDerailment of proteostasis, the homeostasis of production, function, and breakdown of proteins, contributes importantly to the self‐perpetuating nature of atrial fibrillation (AF), the most common heart rhythm disorder in humans. Autophagy plays an important role in proteostasis by degrading aberrant proteins and organelles. Herein, we investigated the role of autophagy and its activation pathway in experimental and clinical AF.Methods and ResultsTachypacing of HL‐1 atrial cardiomyocytes causes a gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
102
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 84 publications
13
102
0
Order By: Relevance
“…Garcia et al first reported impaired cardiac autophagy characterized by reduced LC3 processing (i.e., a reduced protein expression of LC3BⅡ) with an accumulation of lipofuscin deposit — a potential trigger of AF — in the atrial myocardium in patients with post-operative AF [15]. A pair of studies have shown that in chronic AF patients, the cardiac autophagy characterized by an increased protein expression of LC3BⅡ is induced in the atrial myocardium in association with AMPK or endoplasmic reticulum (ER) stress [13, 14]. Our present findings demonstrated that the atrial gene expression of LC3 was upregulated in the patients with chronic AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia et al first reported impaired cardiac autophagy characterized by reduced LC3 processing (i.e., a reduced protein expression of LC3BⅡ) with an accumulation of lipofuscin deposit — a potential trigger of AF — in the atrial myocardium in patients with post-operative AF [15]. A pair of studies have shown that in chronic AF patients, the cardiac autophagy characterized by an increased protein expression of LC3BⅡ is induced in the atrial myocardium in association with AMPK or endoplasmic reticulum (ER) stress [13, 14]. Our present findings demonstrated that the atrial gene expression of LC3 was upregulated in the patients with chronic AF.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, autophagy may regulate the fatty acid metabolism in cardiomyocytes. Alterations of the autophagy in the atrial muscles of patients with persistent AF [13, 14] or post-operative AF have been reported [15]. Although it is still controversial whether the induction of autophagy has a cardioprotective or detrimental effect in AF, it is possible that autophagy is involved in metabolic remodeling in the atrium in chronic AF patients.…”
Section: Introductionmentioning
confidence: 99%
“…There are strong indications that defective interactions between the ER and mitochondria may contribute to AF pathogenesis. In experimental AF models and AF patients, ER stress is present, which induces autophagy and, thereby, cardiac remodeling [74]. Importantly, overexpression of the ER chaperone GRP78 or prevention of ER stress by treatment with the chemical chaperone 4-PBA protected against cardiac remodeling and AF in experimental cardiomyocytes, Drosophila melanogaster, and a dog model for AF [74].…”
Section: Alterations Of Interactions Between the Er And Mitochondria mentioning
confidence: 99%
“…In experimental AF models and AF patients, ER stress is present, which induces autophagy and, thereby, cardiac remodeling [74]. Importantly, overexpression of the ER chaperone GRP78 or prevention of ER stress by treatment with the chemical chaperone 4-PBA protected against cardiac remodeling and AF in experimental cardiomyocytes, Drosophila melanogaster, and a dog model for AF [74]. Moreover, ER stress may activate mitogen-activated protein kinases (MAPKs), which initiate the mitochondrial apoptotic pathway [75].…”
Section: Alterations Of Interactions Between the Er And Mitochondria mentioning
confidence: 99%
“…Although HL‐1 cells derive from atrial myocytes, they maintain the ability to contract and retain differentiated cardiac morphological, biochemical and electrophysiological properties . HL‐1 cells have thus proven useful as a model for studying contracting cardiomyocytes, because of their organized structure and ability to contract in culture; HL‐1 cells have been used in many studies of myocardial remodelling . Here, we report that calcium signalling plays a pivotal role in regulating gravity alteration‐induced cardiac remodelling through the Ca 2+ /CaMKII/HDAC4 signalling pathway.…”
Section: Introductionmentioning
confidence: 90%